1990
DOI: 10.1139/f90-048
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Growth, and Reproduction of Lake Trout (Salvelinus namaycush) and Yellow Perch (Perca flavescens) after Neutralization of an Acidic Lake Near Sudbury Ontario

Abstract: Bowland Lake, an acidified lake (pH 4.8–5.2), was treated with calcite (CaCO3) in 1983. Neutralization allowed for successful reproduction by reintroduced lake trout (Salvelinus namaycush). Mortality of lake trout embryos and juveniles in field toxicity tests decreased from 52–99% preneutralization to 0–30% postneutralization. The resident yellow perch (Perca flavescens) appeared unaffected by the chemical treatment. Both inter- and intra-specific competition were evident in the growth and body condition of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The low pH water was also accompanied by Al i concentrations at levels high enough to be deleterious to the early life stages of fish. This phenomenon was also reported by Gunn et al (1990), Booth et al (1993) in Ontario, and Barlaup et al (1998) in Norway. Lake liming can then be seen not to provide longlasting or complete protection against acid water inputs.…”
Section: Effects On Water Chemistrysupporting
confidence: 77%
See 2 more Smart Citations
“…The low pH water was also accompanied by Al i concentrations at levels high enough to be deleterious to the early life stages of fish. This phenomenon was also reported by Gunn et al (1990), Booth et al (1993) in Ontario, and Barlaup et al (1998) in Norway. Lake liming can then be seen not to provide longlasting or complete protection against acid water inputs.…”
Section: Effects On Water Chemistrysupporting
confidence: 77%
“…In North America, lake liming was shown to be successful in assisting the recovery of trout populations at the highly acidified Bowland Lake in the Sudbury area (Gunn et al 1990). Once more, reproductive success seemed to be the major determinant of trout recovery, though they also noted an improvement of otolith condition in older trout that could only be due to indirect increases in dissolved calcium (Casselman and Gunn 1992).…”
Section: Effects To Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixing zone was more toxic than the acid water alone (containing about 250 µg · L -1 monomeric Al, pH ~ 4.8, ~32 µM Ca) or the limed water (~90 µg · L -1 monomeric Al, pH ~ 7.0, ~92 µM Ca; see also Section VI.B.2). Lime additions to lakes reduce acid and Al toxicity to fish (Gunn et al, 1990, lake trout, Salvelinus namaycush; Lacroix, 1992Lacroix, , 1996, Atlantic salmon, brook trout), but care must be taken in its application. For example, if water pH rises too high, the Al(OH) 4 -anion could become toxic (Atlantic salmon smolts in enclosure experiments; Skogheim et al, 1987).…”
Section: E Gill Morphology and Al Accumulation: Laboratory And Fieldmentioning
confidence: 99%
“…However, studies from Europe and North America have reported mixed results considering the biological responses to liming (Clair & Hindar 2005). In lakes, liming has often, but not always, induced improvements in fish (Gunn et al 1990;Appelberg & Degerman 1991), phytoplankton (Renberg & Hultberg 1992;Ja¨rvinen, Kuoppamaki & Rask 1995), zooplankton (Stenson & Svensson 1995;Svensson & Stenson 2002) and benthic macroinvertebrates (Carbone, Keller & Griffiths 1998;Persson & Appelberg 2001). Inconsistencies of results among studies may not be surprising, however, given that abiotic and biotic constraints affect biological recovery in context-dependent ways (Yan et al 1996(Yan et al , 2003Binks, Arnott & Sprules 2005).…”
Section: Introductionmentioning
confidence: 99%